Analisis Variasi Suhu Pemanasan Serbuk Batu Basalt Sebagai Bahan Pengisi Ordinary Portland Cement Terhadap Kuat Tekan Beton - Rajiman, Rajiman; Listari, Vita (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
Utilization of basalt scoria stone as one of the building materials that can be one of thealternatives to limestone which has been known as a cement maker and utilizes the availability ofabundant basalt, especially in Lampung which has these natural resources. This research is toanalyze the basalt stone powder and analyze the optimum content at the temperature variation ofthe most effective mixture of basalt stone powder to produce compressive strength of concrete.The research method uses experimental methods at the Bandar Lampung University laboratory.The specimens used were cylinders with a diameter of 10.16 cm and a height of 20cm totaling 63specimens using the DOE method. There are 6 types of mixtures, namely at a temperature of800˚C there are 2 mixes of 3% and 7% basalt stone powder, a temperature of 1200˚C there are 2mixes of 3% and 7% basalt stone powder, and at a temperature of 1600˚C there are 2 mixtures of3% and 7% basalt stone powder. Compressive strength testing is performed at the age of concretetesting 7, 14, and 28 days.The results of the study show that the addition of heated basalt stone powder can increase thecompressive strength of concrete. The compressive strength results in a mixture of temperaturevariations included in the planned compressive strength. The optimum compressive strength valueof 28 days of testing occurred on 3% concrete mix of basalt stone powder at a temperature of1600˚C that is equal to 392 kg / cm².Keywords: Concrete, Basalt Stone and compressive strength